Study of Youth Anxiety Levels on No-Mobile Phone (Nomophobia) in Padang City - Dwi Christina Rahayuningrum; Annisa Novita Sary (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
Smartphones have become a means of communication and information in everyday life. This situation makes a person have a dependency in life on mobile phones. Too often the use of mobile phones will cause Nomophobia to begin with smarthphone addiction, assuming that mobile phone is a very important and inseparable need for life. Currently the problem of Nomophobia has occurred in several countries in the world even in Indonesia, this problem is a psychosocial problem. This study uses an analytical approach with quantitative design. Research was conducted on adolescents of high school in the city of Padang in 2018 with a sample of 147 people. Data was collected through questionnaires. The purpose of this study is to be able to study the level of teen anxiety with mobile phones. This research began in July 2018 at Senior High Schools in Padang City. The results obtained for students' anxiety level is 54.5% of high school teenagers in Padang City experience moderate anxiety, and 47.6% of high school teenagers in Padang City experience moderate nomophobia. There is a relationship between the level of anxiety of high school teenagers towards nomophobia in Padang City.